2012
DOI: 10.1371/journal.pone.0047996
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Protein Profiling Reveals Mitochondrial Oxidative Enzyme Impairment and Restoration in Diet-Induced Obese Mice

Abstract: High-fat diet (HFD) induced obesity and concomitant development of insulin resistance (IR) and type 2 diabetes mellitus have been linked to mitochondrial dysfunction. However, it is not clear whether mitochondrial dysfunction is a direct effect of a HFD, or if mitochondrial function is reduced with increased HFD duration. We hypothesized that the function of mitochondrial oxidative and lipid metabolism functions in skeletal muscle mitochondria for HFD mice are similar, or elevated, relative to standard diet (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 45 publications
1
29
1
Order By: Relevance
“…Earlier studies have shown that HFD downregulates genes necessary for oxidative phosphorylation and mitochondrial biogenesis in mouse skeletal muscles (25,26). In this study, we have examined how HFD affects skeletal muscle metabolism by modulating mitochondrial function and biogenesis.…”
Section: Hfd Decreases Skeletal Muscle Sirt-1 Activity and Mitochondrmentioning
confidence: 98%
“…Earlier studies have shown that HFD downregulates genes necessary for oxidative phosphorylation and mitochondrial biogenesis in mouse skeletal muscles (25,26). In this study, we have examined how HFD affects skeletal muscle metabolism by modulating mitochondrial function and biogenesis.…”
Section: Hfd Decreases Skeletal Muscle Sirt-1 Activity and Mitochondrmentioning
confidence: 98%
“…At a similar time Garcia-Roves also showed that high-fat feeding with daily heparin injections in rats resulted in mitochondrial biogenesis in skeletal muscle [207] and subsequent work by the same lab the following year confirmed that oversupply of dietary lipid produced insulin resistance, despite an increase in mitochondria in muscle [208]. Since the time of these publications, a number of other groups have shown that diets rich in fat increase mitochondrial biogenesis in muscle, despite the fact that the same diets robustly induce whole-body and muscle-specific insulin resistance [209][210][211]. One interpretation of these findings is that skeletal muscle is mounting an appropriate response to the increase in caloric load, by upregulating catabolic pathways, however this response is inadequate or mismatched with the elevation in nutrient intake, thus resulting in ectopic lipid accumulation in muscle and insulin resistance.…”
Section: Rodent Studiesmentioning
confidence: 93%
“…The relationship between metabolic problems, such as obesity, diabetes and elevated lipids, and the expression of Apo has been frequently investigated in the general population (Padrao, Ferreira, Vitorino, & Amado, 2012;Ramachandran et al, 2012;Sadler et al, 2012). Due to antipsychotic medications in SZ and mood stabilisers in BD, those patients have an increased risk for metabolic disturbances and altered lipid metabolism (Gibbons, Thomas, Scarr, & Dean, 2010), ultimately contributing to an increased risk for cardiovascular disease (Meyer et al, 2008).…”
Section: Strength and Limitationsmentioning
confidence: 99%